Radiation-Induced Systemic Sclerosis in a Breast Cancer Patient: A Case Report - Anushka Nitin, Repale; Karasevska , Tetiana (The Ukrainian Scientific Medical Youth Journal, 2025)
systemic sclerosis is a rare chronic autoimmune disease characterized by progressive fibrosis, vascular dysfunction, and immune system activation, leading to significant morbidity. While localized skin fibrosis, known as morphea, is a recognized complication of radiation therapy, the development of systemic sclerosis following radiation exposure remains extremely rare. This case highlights the onset of systemic sclerosis in a breast cancer survivor after receiving adjuvant radiotherapy, emphasizing the complexities of early recognition and management. A fifty-year-old female with no prior history of autoimmune disease presented with progressive skin tightening, Raynaud’s phenomenon, joint stiffness, and difficulty swallowing several months after completing radiation therapy for breast cancer. Diagnostic workup revealed positive anticentromere B antibodies, soft tissue calcinosis, and esophageal dysmotility, confirming the diagnosis of limited systemic sclerosis. The patient was initiated on immunosuppressive therapy, vasodilators, and supportive care for gastrointestinal dysfunction, leading to partial symptomatic improvement. The pathophysiology of radiation-induced systemic sclerosis is not yet fully understood, but it is believed to involve microvascular endothelial damage, immune dysregulation, and fibroblast activation. Existing evidence suggests that radiation therapy may act as a triggering factor in genetically predisposed individuals, leading to the unmasking of latent autoimmune processes. The recent growing number of reported cases supports the need for increased awareness among clinicians regarding the potential link between radiation exposure and systemic autoimmune disorders. Given the increasing use of radiation therapy in oncology, recognizing its potential long-term consequences is essential. Delayed diagnosis can result in irreversible fibrosis, multi-organ involvement, and significant functional impairment, underscoring the importance of vigilance in high-risk patients. A multidisciplinary approach involving rheumatologists, oncologists and supportive care personnel is essential to optimize outcomes. Early intervention with immunomodulatory therapies and targeted symptom management can help mitigate disease progression and improve quality of life. Further research is needed to clarify the mechanisms underlying radiation-induced systemic sclerosis, assess potential risk factors, and develop preventive strategies. Identifying genetic predisposition and immune alterations associated with post-radiation fibrosis may facilitate personalized approaches to screening and early intervention in individuals undergoing radiation therapy. Increasing awareness of this rare but serious complication can lead to earlier diagnosis, timely treatment, and improved prognosis in affected patients.